DEGRADATION OF DISCIPLINE AND RESPECT AMONG 4TH AND 5TH GRADE STUDENTS AT SDIT BUDI MULYO SENTOLO - Amaruddin, Hidar; Mahfuddin, Muhammad Ikhwan (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
This research examines the factors causing the decline in the discipline and respect of students at SDIT Budi Mulyo Sentolo. It explains the role of parents, teachers and schools in overcoming the degradation of students’ character of discipline and respect. This research aims to determine the causes of the decline in students’ character of discipline and respect at SDIT Budi Mulyo Sentolo. To find out the role of parents, teachers and schools in overcoming the degradation of the character of discipline and respect for students at SDIT Budi Mulyo Sentolo. To find out the consequences of failure in character education. This type of research is qualitative to determine the decline in students’ disciplined character and respect at SDIT Budi Mulyo Sentolo. The informants were determined through purposive sampling based on the characteristics of informants who knew about students’ conditions in and outside the school environment. These informants include student guardians, school principals, class teachers and the students concerned. The data collection techniques used by researchers are observation, interviews and documentation. The results of this research are the factors causing the degradation of disciplinary character, namely, not doing homework at home and violating agreed class agreements. Factors that cause a decline in respectful character include misbehaving, saying dirty words, being rude to children who follow other religions, and saying harsh words